Modes of transport & communications - BPI (BPI New Delhi, 2011)
"Modes of Transport & Communication" by BPI India, published in 2011. This 80-page hardcover book explores the development of various means of transport and communication throughout history. It provides insights into the inventions and significant changes that have occurred in these areas, making it a valuable resource for understanding the evolution of transportation and communication technologies